(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Nasrullah (Nasrullah, Nasrullah, Amir Nasrullah, Amir Sayyid Nasrullah, Amir Sayyid Nasrullah Bahodirkhan) (June 1, 1806, Bukhara, Bukhara Emirate - September 21, 1860, Bukhara, Bukhara Emirate) [1] - Ruler of the Bukhara Emirate (1827-1860). A statesman and a commander. [2] The Mangits are the 7th ruler of the Uzbek dynasty and the 5th emir of this dynasty. This article covers the reign of Amir Nasrullo Bukhara.